Ewolucja konstrukcji lokalnych „centrum-prowincja”. Transformacja magnackich minipaństw na Ukrainie prawobrzeżnej w latach 1793–1863 (na przykładzie latyfundiów hrabiów Potockich herbu Pilawa) - Kriwoszeja, Igor (Studia Europaea Gnesnensia, 2010)
The article discusses the place of magnate estates in the structure of the Republic. It is his aim to demonstrate the changes in the structure and character of the estates after the second and third partitions. The analysis of territorial and qualitative transformations of the estates is carried out on the example of latifundia of the Potocki family.